(untitled) (Brazilian Journal of Radiation Sciences, 2015)
Ionization chambers are the most employed dosimeters for precise measurements, as those required in radiotherapy. In this work, a new graphite ionization chamber was developed and characterized in order to compose a primary standard system for the beam dosimetry of the 60Co sources. This dosimeter is a cylindrical type ionization chamber, with walls and collecting electrode made of high-purity graphite, and the insulators and stem made of Teflon®. The walls are 3.0 mm thick, and it has a sensitive volume of 1.40 cm3. The characterization was divided in two steps: experimental and Monte Carlo evaluations. This new dosimeter was evaluated in relation to its saturation curve, ion collection efficiency, polarity effect, short- and medium-term stabilities, leakage current, stabilization time, linearity of response and angular dependence. All results presented values within the established limits. The second part of the characterization process involved the determination of the correction factors, obtained by Monte Carlo simulations. Comparing these correction factors values with those from other primary standard laboratories, the highest differences were those for the wall and stem correction factors. The air kerma rate of the 60Co source was determined with this new dosimeter and with the IPEN standard system, presenting a difference of 1.7%. These results indicate that this new dosimeter may be used as a primary standard system for 60Co gamma beams.